Competency-Based Assessment: Challenges and Opportunities for Curriculum Development within Knowledge Societies - Villalobos Rojas, Sebastián (2026)
This narrative review aims to analyze the implementation of competency-based learning in higher education in light of the demands of knowledge societies, serving as a support resource and reflection tool for academic units interested in its incorporation. The review addresses the question: What are the main challenges and opportunities of competency-based education in higher education in this context? A narrative review was conducted of scientific articles and technical documents retrieved from SciELO, Redalyc, Dialnet, and EBSCOhost, complemented by UNESCO sources and State of Education reports. Publications from 2000–2025 were analyzed, focusing on higher education and competency-based training in Latin America. The results contextualize the competency-based approach, identify implementation experiences, and analyze associated challenges and opportunities, such as improving academic and professional training, strengthening employability, integrating cognitive, procedural, and interpersonal dimensions, and fostering pedagogical innovation. Finally, the need for consensual theoretical frameworks, strengthened teacher training, and evaluation strategies coherent with the model is emphasized.